Pendidikan Kesehatan Pertolongan Pertama pada Kecelakaan Meningkatkan Pengetahuan Anggota PMR tentang Penanganan Fraktur - Najihah Najihah; Rahmawati Ramli (FORIKES, 2019)
Accident events in schools are very diverse, for example slipping which causes torn or bruised wounds, dislocation to fractures. A fracture is a breakdown of bone continuity due to a collision or blunt trauma from a particular object. Blunt trauma can cause fractures resulting in internal or external bleeding. To prevent injury to the musculoskeletal system, first aid is needed. This study aims to determine the effect of first aid health education on knowledge of fracture management in PMR members. The research design used was an experiment with a pre-experimental design, one group pretest-posttest design. This study uses nonrobability sampling technique with a purposive sampling approach. The study sample was 22 students who were members of the PMR. The instrument of this study was a questionnaire containing demographic data consisting of name, age, gender, class and duration in the organization and questionnaires about knowledge of fracture handling to be used at pretest and posttest. Data processing used the Mc Nemar statistical test with a significant level of α